2019
DOI: 10.1093/gerona/glz291
|View full text |Cite
|
Sign up to set email alerts
|

Parental History of Dementia Is Associated with Increased Small Vessel Cerebrovascular Disease

Abstract: Background Small vessel cerebrovascular dysfunction that manifests on magnetic resonance imaging (MRI) as white matter hyperintensities (WMH) is linked to increased risk and progression of Alzheimer’s disease (AD), but there is considerable debate about whether it represents a core feature of the disease. Parental history of dementia is a risk factor for AD, suggesting a strong heritable component; the examination of the extent to which parental history of dementia is associated with cerebrov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…However, associations between inherited risk of dementia and SVD have been predominantly examined in cross-sectional studies, reporting largely discrepant findings depending on age cohorts. For instance, 2 studies of older adults, with mean ages of 64 and 74 years, respectively, reported significant associations between heritable risk factors and SVD ( Stamm et al., 2019 ; Wolters et al., 2017 ). Yet, a study of younger adults—aged 52 years old on average—did not find evidence of such an association ( Stefaniak et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, associations between inherited risk of dementia and SVD have been predominantly examined in cross-sectional studies, reporting largely discrepant findings depending on age cohorts. For instance, 2 studies of older adults, with mean ages of 64 and 74 years, respectively, reported significant associations between heritable risk factors and SVD ( Stamm et al., 2019 ; Wolters et al., 2017 ). Yet, a study of younger adults—aged 52 years old on average—did not find evidence of such an association ( Stefaniak et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…(4) Similarly for imaging studies, several studies have found that rst degree relatives of patients with a family history of dementia had an increased risk of small vessel disease, white matter hyperintensities, hypoperfusion, and beta amyloid and tau. (1,(5)(6)(7) As these studies generally focus on older populations in whom some degree of neurodegenerative pathology is likely, they are limited in their ability to distinguish neurodevelopmental from neurodegenerative processes. (1,8,9) One paediatric study investigated the effect of dementia family history in 109 children aged 11-16 years, and observed associations with worse memory and global cognition, albeit only in APOE-ε4 carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies examined heritability of AD risk by determining the relationship of having a first-degree family history of AD diagnosis with various risk factors and biomarkers for AD in the proband. These efforts showed that a positive family history is related to regional brain hypometabolism on FDG-PET 9 , higher amyloid burden on PiB-PET 9 , higher amyloid and pathological tau burden in CSF 10 , higher white matter hyperintensity volume 11 , decreased temporal cortex activation on functional MRI 12 , lower brain volume on structural MRI 13 , lower white matter integrity on diffusion tensor imaging (DTI) 14 , and worse cognitive performance 15 . These studies generally relied on retrospective assessment of parental diagnostic status, which is susceptible to recall bias, and on clinic-based samples comprising primarily Non-Hispanic White participants, which do not represent the growing diversity of older adults and those disproportionately affected by the disease 5 .…”
Section: Introductionmentioning
confidence: 99%